Renormalization Group and Fixed Points in Quantum Field Theory - Hollowood, Timothy J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This Brief presents an introduction to the theory of the renormalization group in the context of quantum field theories of relevance to particle physics. Emphasis is placed on gaining a physical understanding of the running of the couplings. The Wilsonian version of the renormalization group is related to conventional perturbative calculations with dimensional regularization and minimal subtraction. An introduction is given to some of the remarkable renormalization group properties of supersymmetric theories.
The concept of the Renormalization Group -- Scalar Field Theories -- RG and Perturbation Theory -- Gauge Theories and Running Couplings -- RG and Supersymmetry.
Keywords: Physics; Quantum theory; Physics; Quantum Field Theories, String Theory; Elementary Particles, Quantum Field Theory; Mathematical Applications in the Physical Sciences; Mathematical Physics